Evaluation of recycled concrete aggregates for their suitability in construction activities: An experimental study. (February 2017) - Puthussery, Joseph V.; Kumar, Rakesh; Garg, Anurag
Highlights: Heavy metal leaching from waste concrete aggregates was determined. Based on particle size characteristics, recycled fine aggregates were classified as well graded sand. Effect of recycled coarse and fine aggregates on the strength of concrete was found. Recycled aggregates showed immense potential of being used in construction activities. Abstract: Construction and demolition waste disposal is a major challenge in developing nations due to its ever increasing quantities. In this study, the recycling potential of waste concrete as aggregates in construction activities was studied. The metal leaching from the recycled concrete aggregates (RCA) collected from the demolition site of a 50 year old building, was evaluated by performing three different leaching tests (compliance, availability and Toxic Characteristic Leaching Procedure). The metal leaching was found mostly within the permissible limit except for Hg. Several tests were performed to determine the physical and mechanical properties of the fine and coarse aggregates produced from recycled concrete. The properties of recycled aggregates were found to be satisfactory for their utilization in road construction activities. The suitability of using recycled fine and coarse aggregates with Portland pozzolanic cement to make a sustainable and environmental friendly concrete mix design was also analyzed. No significant difference was observed in the compressive strength of various concrete mixes prepared by natural and recycled aggregates. However, only the tensile strength of the mix prepared with 25% recycled fine aggregates was comparable to that of the control concrete. For other mixes, the tensile strength of the concrete was found to drop significantly. In summary, RCA should be considered seriously as a building material for road construction, mass concrete works, lightly reinforced sections, etc. The present work will be useful for the waste managers and policy makers particularly in developing nations where proper guidelines are still lacking.